Live sports media the what, how and why of sports broadcasting - Deninger, Dennis (Routledge, 2022)
"In Live Sports Media: The What, How and Why of Sports Broadcasting, Dennis Deninger provides an all-encompassing view of the sports television industry from his own perspective as an Emmy award-winning producer at ESPN, at a time of seismic shifts in the industry. Technological advances and the proliferation of sports content across multiple media platforms have increased accessibility to sports events of all kinds across the world. Shifts in viewing habits and audience preferences are changing the dynamic of the sports media and the sports industry as a whole. The result: more power for some sectors and diminished power for many others, to which professionals in the field need to rapidly adapt. This second edition has been substantially updated to explore the impact of COVID-19 disruptions on sports, the growth of women's sports broadcasting and evolving sports, as well as political statements made in sports, Black Lives Matter, and "taking a knee." It illustrates the origins, impact, reach, economics, production, and presentation of sports on video media--including, but not limited to, television. It takes the reader behind the scenes to describe the forces and processes that have shaped and continue to change sports content, its delivery and how it connects with fans. Dennis Deninger draws from his experiences as an expert in the industry to expose how the choices and decisions that are now being made affect the programming, content, storytelling, production, advertising, and delivery of the sports broadcasting that we will see next season, and how it will evolve in the years to come. This practical, entertaining book provides insights into sports broadcasting that sports management, media, and journalism students and learning practitioners will not find anywhere else"-- Provided by publisher.